PHYTOCEMICALS SCREENING AND CELL CYCLE ARREST ACTIVITY OF n-HEXANE EXTRACT OF Vernonia amygdalina Delile LEAVES AGAINST PANCREATIC CANCER CELL LINE - Fauzan, M L; Hasibuan, P A Z; Harahap, U (Asian Journal of Pharmaceutical Research and Development, 2019)
Objective: This study aims to determined phytochemical compounds of simplex and n-hexane extract (nHE) of Vernonia amygdalina Delile Leaves and cell cycle arrest activity against PANC-1 cells. Methods: The leaves of Vernonia amygdalina Delile were dried and extracted with n-hexane, followed by evaporation and freeze-drying. Phytochemicals screening were analyzed with standard procedures. Cytotoxic activity was carried out using MTT assay method. PANC-1 cells were treated with different concentrations of nHE (500 ug/mL, 250 ug/mL, 125 ug/mL, 61.5 ug/mL and 31.25 ug/mL) for 24 hours to obtained IC50 values. The cell cycle inhibition activity of nHE was carried out used flowcytometry method and apoptosis activity used double staining method. Results: Then HE was identified contains steroids/triterpenoids. The IC50 was114.80 ± 1.21 ug/mL. The nHE inhibited cell cycle PANC-1 on M1 phase (67.39%) and it was induced apoptosis process on PANC-1 cells. Conclusions: Our results suggest that extractsn-hexane of Vernonia amygdalina Delile Leaves had as cancer chemoprevention activities with inhibits cell cycle and spur apoptosis process on PANC-1 cells. Keywords: